The Bible for Children: the Emergence and Development of the Genre, 1550-1990 - Bottigheimer, Ruth B. (Studies in church history, 1994)
Books for children have existed for centuries. Their contents range from instructional manuals to flights of fancy. In children’s literature, a variety of narrative forms have emerged, developed, flowered, and faded, but one genre, Bible stories for children’s use, has remained in existence as long as print itself.